Plant materials for gastrointestinal diseases used in Chawang District, Nakhon Si Thammarat Province, Thailand. (24th December 2016) - Neamsuvan, Oratai; Phumchareon, Thanchanok; Bunphan, Wanisa; Kaosaeng, Wayanan
Abstract: Ethnopharmacological relevance: In Thailand, gastrointestinal diseases have occurred since the past, consequently healers know well how to use herbs for treatment. Currently, some groups of Thai people continue to be interested in treating diseases by herbs. Therefore, the aims of this study were to (1) compile a list of species of medicinal plants and their source, (2) document the diseases treated and their frequency of citation, (3) record the parts used, methods of preparation and route of administration of traditional medicines, and (4) compare the folk knowledge to that in other relevant reports. Materials and methods: Ten folk healers were included in the study. Semi-structured interviews were used to compile data, namely plant parts used, preparation, route of administration and properties. The data were analyzed by interpretation and descriptive statistics. Results: Sixty-two species in 28 families were identified. The most used plants (11 species) were grouped in Zingiberaceae. The highest level of relative frequency of citation (RFC) was found in Zingiber officinale Roscoe (1.0). Most plants were applied for treating constipation. Powder was the most common preparation form of folk drug. A total of 174 use lists were recorded, however, more than two thirds were reported as new uses in this study. Conclusion: A literature review revealed that the remaining 37 species for pharmacological activities and 42 species for toxicity should be further studied to validate the folk use of these medicinal resource. Graphical abstract: